2021
DOI: 10.1007/s10943-021-01352-0
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Catholic Priests: A Scoping Review of the Literature

Abstract: This study offers an exploratory review of the experience of stress and burnout syndrome among Catholic priests. Following Arksey and O’Malley's (Int J Soc Res Methodol 8(1):19–32, 2005, 10.1080/1364557032000119616)  protocol, a scoping study was conducted. Given the scarcity of studies found on the subject, a broad selection criterion  was used, which included quantitative, qualitative and mixed studies, literature reviews and comparative studies with other professions. The results reveal various risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…However, depending on the importance of a given factor for the individual and his/her emotional response, they may lead to changes in the body that will result in loss of health [ 3 , 6 ]. The most commonly confirmed health consequences of occupational stress include coronary heart disease [ 7 , 8 , 9 , 10 ], alcoholism, and psychiatric disorders [ 11 ]. Stress may correlate with the risk of metabolic syndrome [ 12 ], acute myocardial infarction [ 13 ], type 2 diabetes [ 14 , 15 ], and renal dysfunction [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the importance of a given factor for the individual and his/her emotional response, they may lead to changes in the body that will result in loss of health [ 3 , 6 ]. The most commonly confirmed health consequences of occupational stress include coronary heart disease [ 7 , 8 , 9 , 10 ], alcoholism, and psychiatric disorders [ 11 ]. Stress may correlate with the risk of metabolic syndrome [ 12 ], acute myocardial infarction [ 13 ], type 2 diabetes [ 14 , 15 ], and renal dysfunction [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also report that stress and burnout are associated with factors such as smoking, alcoholism, obesity, diabetes, cardiovascular disease, anxiety and depression. Strengthening protective factors and minimizing the impact of risk factors would greatly contribute to the improvement of the health of the clergy profession (Ruiz-Prada et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…preventive examinations or follow-up visits (Avdeenko et al, 2019 ). A few studies confirm that this population is equally highly exposed to health problems, including stress and occupational burnout (Büssing et al, 2013 ; Ruiz-Prada et al, 2021 ), overweight and obesity, (Henein et al, 2021a , 2021b ; Proeschold-Bell & LeGrand, 2010 ), cardiovascular disease (Ike et al, 2007 ), hypertension (Henein et al, 2021a , 2021b ). The priests themselves notice the need for screening tests to prevent hypertension and stress (Moceri & Cox, 2019 ).…”
Section: Introductionmentioning
confidence: 96%
“…Clergy report high levels of stress; a literature review of clergy mental health articles from 1975 to 2000 found high levels of occupational stress across denominations and attributed the stress to “extraordinary demands,” criticism, congregational conflicts, and expectations of clergy family members (Weaver et al, 2002 , p. 398). A more recent scoping review of Catholic priests attributed stress to work overload, lack of boundaries, and perfectionistic personality styles (Ruiz-Prada et al, 2021 ). Clergy exhibit physical health indicators of chronic stress, including diabetes, hypertension, asthma, joint-related disease, cardiovascular disease, and obesity (Baruth et al, 2014 ; Halaas, 2002 ; Proeschold-Bell & LeGrand, 2010 ).…”
Section: Introductionmentioning
confidence: 99%